Penerapan Otomatisasi Sistem Instalasi Pipa Penyiraman Untuk Pendinginan Greenhouse Pada Kelompok Usaha Mikro Cahaya Farm Di Carang Pulang Bogor - Handini, Wike; Widanti, Nurdina; Witdi Yanto, Nur; Wiji Lestari, Sri; Herliati, Herliati; Novria Sonjaya, Abeth; Sekar Ningrum, Sari; Widyawati, Yeti (Dedikasi:Jurnal Pengabdian kepada Masyarakat, 2025)
The process of hydroponic plant cultivation in the Cahaya Farm Micro Business Group's greenhouse is hindered by the fact that the temperature in the greenhouse, especially during the day, rises to 37°C. The elevated temperatures characteristic of the dry season has been shown to adversely affect the quality of lettuce, thereby reducing the overall yield and, consequently, the revenue generated from its cultivation. The primary objective of this initiative is to facilitate the installation of a pipe system and a sprayer that can operate automatically to reduce the temperature in the greenhouse. This is expected to enhance community well-being and reduce unemployment. The engineering of the design of equipment installation, the procurement of components, the installation of a watering system for cooling, and the surveying of satisfaction with the results of PkM performance require stages that must be executed with the requisite calculations. Presently, the nozzle installed on the roof of the greenhouse is operational, as are the automatic timer and application MQTT (Message Queuing Telemetry Transport) dashboard. The Campus PkM program's trainee assessment demonstrated notable success, with an average score of 3.77 out of a 4.00 scale, representing 94.13% of the maximum attainable score. This observation was particularly evident in the domains of teacher quality and empathy, as evidenced by the attainment of scores of 3.89 and 4.00, respectively.